Prawo pacjenta do informacji według przepisów polskiego prawa medycznego - Bączyk-Rozwadowska, Kinga (Studia Iuridica Toruniensia, 2011)
<!–[if gte mso 9]> <![endif]–> A patient’s consent is the legal basis for any medical intervention only when it is preceded by the appropriate information given to the patient by a doctor (informed consent). The doctor’s duty to inform and the corresponding right of the patient to receive information is embodied in deontological codes, many international documents and resolutions as well as in domestic statutes, of which the most important is the Law of Doctor’s and Dentist’s Profession of 1996 (Article 31) and the Act of Patients’ Rights and Patients’ Ombudsman of 2008 (Article 9). According to the law, information given to a patient (or, in the case where he is unable to receive it, to his legal representative or a competent “close person”) should be clear, transparent, understandable for a certain patient (as a layperson) and communicated in a suitable (proper) time before the treatment. The scope and object of information is very broad, since doctor is obliged to inform a patient about his health condition, suggested and possible diagnostic and treatment methods, foreseeable consequences of their application or omission, results of treatment and prognoses for the future. The information should comprise, as a rule, only the normal (typi- cal, ordinary) risks and side eff ects which may appear in the case of a certain patient. However, a patient has “a right to know the truth” and on his request, the doctor should provide him with full information, including also all the extraordinary consequences and complications that appear very rarely (exceptionally). The doctor who by his fault infringes patient’s right to be informed may bear civil liability for non-pecuniary loss on the grounds of Article 4 of the Act of Patients’ Rights and Patients’ Ombudsman. The burden of proof of having performed the obligation to inform rests on a doctor (Article 6 of the Civil Code). He must then prove that the information granted by him on the risks and consequences of the treatment served as a basis for the patient’s consent to particular medical intervention or its refusal. <!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>